2017
DOI: 10.1002/prp2.331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mTOR inhibition on cardiac and adipose tissue pathology and glucose metabolism in rats with metabolic syndrome

Abstract: The mammalian target of rapamycin (mTOR) is a regulator of metabolism and is implicated in pathological conditions such as obesity and diabetes. We aimed to investigate the role of mTOR in obesity. A new animal model of metabolic syndrome (MetS), named DahlS.Z‐Lepr fa/Lepr fa (DS/obese) rats was established previously in our laboratory. In this study, we used this model to evaluate the effects of mTOR inhibition on cardiac and adipose tissue pathology and glucose metabolism. DS/obese rats were treated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Similarly to muscle and adipose tissue, mTORC1 activity was observed to be increased in the livers of obese rodents, resulting in the degradation of insulin receptor substrate 1 and the onset of hepatic insulin resistance [36]. A recent study by Uchinaka et al reported that the activation of mTOR signaling contributes to MetS pathophysiology and associated complications [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to muscle and adipose tissue, mTORC1 activity was observed to be increased in the livers of obese rodents, resulting in the degradation of insulin receptor substrate 1 and the onset of hepatic insulin resistance [36]. A recent study by Uchinaka et al reported that the activation of mTOR signaling contributes to MetS pathophysiology and associated complications [38].…”
Section: Discussionmentioning
confidence: 99%
“…LV, kidney, VAT, or SAT tissue was analyzed by hematoxylin-eosin (H&E), Azan-Mallory, or periodic acid–Schiff (PAS) staining as well as by immunohistochemical staining for the monocyte–macrophage marker CD68 (antibody clone ED-1, diluted 1:100; Chemicon, Temecula, CA, USA), as previously described 19 , 20 . The glomerulosclerosis index (GSI) was measured for 50 glomeruli in PAS-stained sections of each rat, also as described previously 21 .…”
Section: Methodsmentioning
confidence: 99%
“…An animal model showing metabolic syndrome characteristics, where mTOR pathway inhibitors were administered, was analyzed. As a result, a reduction in oxidative stress (decrease in superoxide production and NADPH oxidase activity) and inflammatory response (reduction of macrophage influx), weight loss, reduction of adipose tissue hypertrophy, and hypertension were observed, which was beneficial to the cardiovascular system and reduced the risk of cardiometabolic complications [71]. Thus, cerebral insulin resistance in schizophrenia may induce reduced signal transduction for gamma-aminobutyric acid (GABA), N-methyl-d-aspartic acid (NMDA), dopamine-D2 receptors, and reduced levels of brain-derived neurotrophic factor (BDNF).…”
mentioning
confidence: 99%